1983
DOI: 10.1016/0143-974x(83)90011-1
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic beam buckling experiments

Abstract: This report is one of a continuing series of Research Reports published by the Department of Civil Engineering at the University of Queensland. This Department also publishes a continuing series of Bulletins. Lists of recently published titles in both of these series are provided inside the back cover of this report. Requests for copies of any of these documents should be addressed to the Departmental Secretary. The interpretations and opinions expressed herein are solely those of the author(s). Considerable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 1 publication
0
27
0
4
Order By: Relevance
“…Since this study focuses on the LTB strengths of steel beams, the experiments carried out by Dux and Kitipornchai [26] to investigate out-of-plane instability effects in steel beams of different lengths and subjected to a variety of moment gradient shapes, were chosen to validate the finite element models. In the experiments, the specimens, made up of UB 254x146 universal beam sections, were subjected to point loads along the span, while torsional and lateral restraints were provided at the points of load application.…”
Section: Validation Of Finite Element Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this study focuses on the LTB strengths of steel beams, the experiments carried out by Dux and Kitipornchai [26] to investigate out-of-plane instability effects in steel beams of different lengths and subjected to a variety of moment gradient shapes, were chosen to validate the finite element models. In the experiments, the specimens, made up of UB 254x146 universal beam sections, were subjected to point loads along the span, while torsional and lateral restraints were provided at the points of load application.…”
Section: Validation Of Finite Element Modelsmentioning
confidence: 99%
“…In the experiments, the specimens, made up of UB 254x146 universal beam sections, were subjected to point loads along the span, while torsional and lateral restraints were provided at the points of load application. The material properties and cross-section dimensions reported by [26] for each specimen were used within the finite element models. Moreover, the measured values of geometrical imperfections (lateral bow and initial twist) provided by [26] were incorporated into the finite element models assuming them as a half-sine wave in shape for each laterally unrestrained span.…”
Section: Validation Of Finite Element Modelsmentioning
confidence: 99%
“…Initial out-of-straightness is normally expressed as a fraction of the length, L, of the member (about L/l000). Dux and Kitipornchai (1981) and Essa and Kennedy (1993) demonstrated that most hot-rolled wide flange sections tend to have initial out-of-straightness close to maximum permissible tolerances. Information on welded build-up shapes can be found in Alpsten and Tall, 1970;McFalls and Tall, 1970;Alpsten, 1972;Brozzetti et al, 1970b;and Bjorhovde et al, 1972) but is not discussed here.…”
Section: A-2mentioning
confidence: 99%
“…are plotted with theoretical capacities (14) and experimental results (3,6) in Figure 5. Several buckling formulae which approximate the theoretical capacity curves of Reference (14) have been proposed.…”
Section: (9)mentioning
confidence: 99%
“…The analysis method for determinate inelastic laterally continuous beams is an extension of the elastic beam analysis previously proposed by the authors (4,6). The critical segment is assumed to hav e reduced uniform rigidities, the change being determined by a stiffness modification factor.…”
Section: (V)mentioning
confidence: 99%